TOURISM DEVELOPMENT IN THE WORLD CULTURAL HERITAGE AREA OF SUBAK JATILUWIH, TABANAN, BALI - Susila, I Gede (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2018)
Subak Jatiluwih in Tabanan Regency, Bali, has double status. On the one hand the Subak (water irrigation system) is a tourist attraction (destination), and on the other hand its status is as World Cultural Heritage (Warisan Budaya Dunia or WBD). Related to that matter, this paper describes two things: (1) the development of tourism facilities in Subak Jatiluwih area, and (2) the financial input in managing Jatiluwih tourist attraction and its distribution. This is a qualitative study. The data found is analyzed using qualitative data analysis. The result of study shows that, regarding the double status as stated above, it is precisely within the perceptions of local community about the status of Subak Jatiluwih as WBD are related to